Quality Of Service, Price And Location On Customer Satisfaction (Case Study Of Agricultural Materials, Vito Subur Utama) In Solok Selatan District - Maya Rahmi Santika; Alfian Alfian (Universitas 45 Surabaya, 2023)
This study aims to examine service quality, price and location on consumer satisfaction (a case study of Vito Fertile Main Agricultural Materials) in Solok Selatan district. This type of research is quantitative, where the research process emphasizes objective measurement of results using statistical analysis. The population in this study are all consumers as much as 61 people. The sampling technique used is the probability sampling technique used with the accidental sampling method, where the sample is based on coincidence with the sample size taken using the formula (Hair et al., n.d.). the hair formula is used because the population size is not known with certainty and suggests a minimum sample size of 5 to 10 times the indicator variable so that the number of variables , while the number of samples was 61 people obtained from the main fertile vito consumers. The type of data used in this research is quantitative and qualitative data. While the data sources are primary and secondary data sources. Data collection techniques using questionnaires and literature study. using instrument testing (validity test, reliability test and descriptive analysis), classic assumption test (normality test, multicollinearity test and heteroscedasticity test) then multiple linear regression and hypothesis testing with the help of the SPSS application. Where is the multiple linear regression Y = 18.027 + 0.503 X1 + 0.377 X2 + 0.603 X3 and the first hypothesis test shows that the t-count value is greater than t-table (2.202 > 1.98197) with a significantly smaller value than the alpha value (0.034 <0 .05) this shows that H1 is accepted, which means that service quality has a positive effect on customer satisfaction and the second hypothesis test shows that the t-count value is greater than t-table (2.543 > 1.98197) with a significantly smaller value than the alpha value (0.048 <0.05) this shows that H2 is accepted, which means that price has a positive effect on consumer satisfaction and the third hypothesis test shows that the t-count value is greater than t-table (4.436 > 1.98197) with a significantly smaller value than the alpha value ( 0.000 <0.05) this shows that H3 is accepted, which means that location has a positive effect on customer satisfaction. The results of the study show that service quality has a positive and significant effect on customer satisfaction, price has a positive and significant effect on customer satisfaction and location has a positive and significant effect on customer satisfaction.